Theileria parva: influence of vector, parasite and host relationships on the epidemiology of theileriosis in southern Africa - Norval, R.A.I.; Lawrence, J. A.; Young, A.S.; Perry, Brian D.; Dolan, T. T.; Scott, J. (Cambridge University Press, 1991)
The protozoan parasite Theileria parva, transmitted by the ixodid tick Rhipicephalus appendiculatus, is the cause of East Coast fever (ECF) and the related syndromes of Corridor disease and January disease in cattle of eastern, central and southern Africa. It is likely that buffalo (Syncerus caffer) are the natural host of T. parva. In eastern and southern Africa, there exist both buffalo-adapted and cattle-adapted T. parva. Disease caused by buffalo-adapted parasites is called Corridor disease, and that caused by cattle-adapted parasites is termed East Coast fever. In eastern Africa, it has been shown experimentally that buffalo-adapted T. parva can, after serial passage in cattle, become adapted to cattle, in which it can then be maintained and cause ECF. This adaptation has been termed transformation. The transformation of buffalo-adapted T. parva to a cattle-adapted parasite has not been reported in southern Africa, and ECF, eradicated from South Africa, Swaziland and southern Mozambique by 1960, has not reappeared in the subcontinent. This paper discusses the possible reasons for this, and hypothesizes that vector population dynamics and the susceptibility of the vector population to infection with T. parva are among the most important factors which influence the expression of ECF as a disease entity, and the likelihood of transformation occurring. It also considers the possibility that disappearance of ECF from southern Africa resulted from the extinction, as a result of vigorous control measures and unfavourable climatic conditions, of non-diapausing populations of R. appendiculatus that may have been introduced from eastern Africa with cattle imported in 1901.